Dial the Mechanism Switch of VN from Conversion to Intercalation toward Long Cycling Sodium‐Ion Battery. Issue 12 (12th February 2020) - Wei, Shiqiang; Wang, Changda; Chen, Shuangming; Zhang, Pengjun; Zhu, Kefu; Wu, Chuanqiang; Song, Pin; Wen, Wen; Song, Li
Abstract: Transition metal nitrides are promising energy storage materials in regard to good metallic conductivity and high theoretical specific capacity, but their cycling stability is impeded by the huge volume change caused by the conversion reaction mechanism. Here, a simple strategy to produce an intercalation pseudocapacitive‐type vanadium nitride (VN) by one‐step ammonification of V2 C MXene for sodium‐ion batteries is reported. Profiting from a distinctive layered structure pillared by Al atoms in the layer spacing, it delivers a high capacity of 372 mA h g −1 at 50 mA g −1 and a desirable rate performance. More importantly, it shows remarkably long cycling stability over 7500 cycles without capacity attenuation at 500 mA g −1 . As expected, it is found that the intercalation pseudocapacitance plays an important role in the excellent performance, by using in situ X‐ray diffraction and ex situ X‐ray absorption structure characterization. Even more remarkable, are the high energy and power density of the sodium‐ion capacitor after coupling with a carbon‐based cathode. The hybrid device possesses an energy density of 78.43 Wh kg −1 at power density of 260 W kg −1 . The results clearly show that such a unique‐layered VN with outstanding Na storage capability is an excellent new material for energy storage systems. Abstract : Layered vanadium nitride (VN) pillared by Al atoms is reported with outstanding Na + storage performance and its intercalation pseudocapacitive mechanism is verified by ex situ XAS and in situ XRD measurements. The dynamics of sodium ions in this layered VN anode are analyzed to explain its pseudo‐capacitance contribution. Moreover, a sodium‐ion hybrid capacitor is constructed to demonstrate practical applications.